IMPLEMENTASI NILAI-NILAI ISLAM DI KOPERASI JASA KEUANGAN SYARIAH BMT CEHA ALMARZUQI DUKUN GRESIK TERHADAP LOYALITAS NASABAH - Duta Bintan Fitriyah; Robbah Khunaifih; Nailis Sa’adah (Bajang Institute, 2022)
Islamic values ​​are actually the accumulation of life principles that teach about how a person should conduct his daily life, one principle with another mutually reinforcing. There is no exception for Islamic values ​​that are carried out by micro-scale Islamic financial institutions such as BMT (Baitul Maal Wat Tamwil). BMT CeHa Al-Marzuqi as one of the Islamic microfinance institutions has these Islamic values ​​in carrying out its activities. In addition to the administrator or manager doing this, of course, members are also expected to do so. In this way, members' loyalty to the institution becomes more than having to choose another institution. Not infrequently members who do not pay attention to these value principles have very doubtful loyalty. The method of data collection is done by interviewing members/customers who are doing daily transactions at BMT then processed by data analysis techniques and presented clearly and actually. The Islamic values ​​include etiquette or morality, such as greeting members/customers who enter the office, greetings when they meet on a trip, praying for each other among members or administrators in terms of goodness and doing things that are justified according to the rules. - the rules or norms of Islamic law. Thus emerged a sense of bellonging or a sense of belonging to each other in order to provide benefits to the surrounding environment